Use of Alkylarsonium Directing Agents for the Synthesis and Study of Zeolites. Issue 71 (22nd November 2019) - Sáez‐Ferre, Sara; Lopes, Christian W.; Simancas, Jorge; Vidal‐Moya, Alejandro; Blasco, Teresa; Agostini, Giovanni; Mínguez Espallargas, Guillermo; Jordá, Jose L.; Rey, Fernando; Oña‐Burgos, Pascual
Abstract: Expanding the previously known family of ‐onium (ammonium, phosphonium, and sulfonium) organic structure‐directing agents (OSDAs) for the synthesis of zeolite MFI, a new member, the arsonium cation, is used for the first time. The new group of tetraalkylarsonium cations has allowed the synthesis of the zeolite ZSM‐5 with several different chemical compositions, opening a route for the synthesis of zeolites with a new series of OSDA. Moreover, the use of As replacing N in the OSDA allows the introduction of probe atoms that facilitate the study of these molecules by powder X‐ray diffraction (PXRD), solid‐state nuclear magnetic resonance (MAS NMR), and X‐ray absorption spectroscopy (XAS). Finally, the influence of trivalent elements such as B, Al, or Ga isomorphically replacing Si atoms in the framework structure and its interaction with the As species has been studied. The suitability of the tetraalkylarsonium cation for carrying out the crystallization of zeolites is demonstrated along with the benefit of the presence of As atoms in the occluded OSDA, which allows its advanced characterization as well as the study of its evolution during OSDA removal by thermal treatments. Abstract : As organic structure‐directing agents : Tetraalkylarsonium cations, a novel member of the ‐onium (ammonium, phosphonium, and sulfonium) family of organic structure‐directing agents for the synthesis of zeolites, are presented for the first time. These cations permit the synthesis of the zeolite ZSM‐5 as well as serving as probes for the study of the zeolite and the occluded cation by several techniques, as powder XRD, solid‐state NMR spectroscopy, and XAS.